Adrenalectomies for adrenal gland tumours-a retrospective study of 15 cases at a single center - Kalabhavi, Srinivas; Kanagali, Revanasiddappa; Makannavar, Pramod; Benthur, Sangamanth; Aradhya, Bhuvanesh (International Surgery Journal, 2021)
We present our experience of 15 cases of adrenal tumours who underwent adrenalectomy procedure in last 5 years at our institute and analysed retrospectively clinical outcome. Pre-operative, intra-operative and post-operative data from 15 patients who underwent adrenalectomy between August2015 and July 2020 at our institution were retrospectively collected and reviewed. Diagnosis was obtained on the basis of clinical examination, laboratory values and imaging techniques. Prazosin was preoperatively administered in case of pheochromocytoma. All adrenalectomies were performed by team of urologists. A multidisciplinary management involving endocrinologists, urologists, oncologists, onco-surgeons and anaesthesiologists was carried at our institute. Fifteen patients were evaluated retrospectively in our study. Functioning tumours were diagnosed in 08(53.3%) patients, 06 patients were affected by pheochromocytomas, 2 cases by adrenal cortical carcinoma (ACC). 3 (20%) patients had incidentalomas. 11 (73.3%) patients underwent open adrenalectomy and in 04 (26.6%) patients, laparoscopic adrenalectomy (LA) was performed. An accurate preoperative examination (radiological and biochemical evaluation) is mandatory to select eligible patients to LA or open adrenalectomy (OA). LA is safe and feasible for benign lesions up to 6 cm. A skilled operative team, composed by surgeons experienced in LA after adequate learning curve, is required. Preoperative alfa blockade does not prevent PCC hypertensive crises but, facilitating their pharmacological control, must be recommended.